Looking for new emperor penguin colonies? Filling the gaps - André Ancel; Robin Cristofari; Phil N. Trathan; Caroline Gilbert; Peter T. Fretwell; Michaël Beaulieu (Global Ecology and Conservation, 2017)
Detecting and predicting how populations respond to environmental variability are crucial challenges for their conservation. Knowledge about the abundance and distribution of the emperor penguin is far from complete despite recent information from satellites. When exploring the locations where emperor penguins breed, it is apparent that their distribution is circumpolar, but with a few gaps between known colonies. The purpose of this paper is therefore to identify those remaining areas where emperor penguins might possibly breed. Using the locations of emperor penguin breeding colonies, we calculated the separation distance between each pair of geographically adjacent colonies. Based on mean separation distances between colonies following a circumpolar distribution, and known foraging ranges, we suggest that there may yet be six undiscovered breeding locations with half of these in Eastern and the remainder in Western Antarctica. Productivity in these regions suggests that food resources are likely to sustain emperor penguin populations. Our analysis highlights a fundamental requirement, that in order to predict how species might respond to regional climate change, we must better understand their biogeography and the factors that lead to their occupation of particular sites. Regarding emperor penguins, remote sensing should target the identified gaps apparently devoid of penguins in order to update the total number of colonies, to re-evaluate both the regional and global population of emperor penguins, and to gain a better understanding of their biogeography.